THE KNOWLEDGE OF INFORMATION TECHNOLOGY OF THE PORTUGUESE - BULKA, Beata; Justyna, KOS (Trends in education, 2010)
The article presents the results of research on the knowledge of Information Technology of the Portuguese. The research were conducted among 160 people in Portugal.
Keywords: Informational Technology; Portuguese; competence.